An unusual case of epidermolysis bullosa complicated by persistent oligoarticular juvenile idiopathic arthritis; lessons to be learned - Eleftheriou Despina; Mellerio Jemima E; Martinez Anna E; Maritsi Despoina; Pilkington Clarissa A (BMC, 2011)
Abstract Recessive Dystrophic Epidermolysis Bullosa (RDEB) is a rare and severe hereditary skin disease. Oligoarticular Juvenile Idiopathic Arthritis (JIA) although infrequent in the general paediatric population, is the most frequent type of autoimmune joint disease in children. While different in aetiology, both diseases are characterized by gradual deterioration in mobility and function. We report a female patient, diagnosed with RDEB at birth, who presented with inflammatory bowel disease (IBD) at the age of four years, and subsequently developed oligoarticular JIA at seven years of age, and discuss the diagnostic and treatment challenges of this unusual case. This report, besides presenting a unique case, also highlights the important issues that need to be taken into account when assessing and managing patients with such complex conditions.